De novo SNP discovery and strong genetic structuring between upstream and downstream populations of Paratya australiensis Kemp, 1917 (Decapoda: Caridea: Atyidae). Issue 2 (14th February 2018) - Rahman, Sharmeen; Schmidt, Daniel; Hughes, Jane
Abstract: The Australian glass shrimp, Paratya australiensis  Kemp, 1917 (Atyidae) has been used in population genetics studies in freshwater ecosystems. There are nevertheless no genome wide markers and no reference genome developed for this species. We used the next generation sequencing (NGS) technique, restriction site associated DNA sequencing (RAD-seq) to genotype thousands of single nucleotide polymorphism (SNP) markers across the genome of P . australiensis . A total of 47 individuals from Booloumba Creek in the Mary River catchment, Conondale Range, Queensland, Australia were sequenced using a double digest RAD-seq approach. De novo assembly produced a total of 476, 055 tags in the catalog. Due to missing data, a few individuals were filtered out and 2, 330 loci were genotyped from 39 individuals. Upstream genetic diversity (Hexp = 0.2258, average across loci) was slightly lower than downstream diversity (Hexp = 0.2422, average across loci). PCA and admixture analysis showed clear divergence between the two populations, whereas a Bayesian tree indicated that only a single mitochondrial DNA (mtDNA) lineage was present in the stream. Due to long-term isolation and very little dispersal, the populations have diverged significantly at nuclear loci, although divergence was minimal at the mtDNA COI fragment analysed. This study facilitated evaluation of new markers in this species, as well as highlighting genetic structuring and diversity between populations of a stream using a large data set (thousands of SNP markers) compared to few markers used in previous studies.